Do Speed Limit Reductions Help Road Safety? : Lessons from the Republic of Korea's Recent Move to Lower Speed Limit on Urban Roads - Mitra, Sudeshna; Job, Soames; Han, Sangjin; Eom, Kijong (World Bank, Washington, DC, 2021)
Significant research has been undertaken on how changes in speed limit—for example, the introduction of 30 kilometers per hour, or kph (20 miles per hour, or mph) speed limits—impact safety both when combined with, and without "traffic-calming" engineering treatments such as speed humps or raised platforms. However, most of the studies have been conducted in Australia or countries in Western Europe, with almost no recorded studies from Asia, Africa, the Americas and Eastern Europe. Though it may be reasonable, a well-developed infrastructural environment such as that found in Korea would expect similar results as that of the western countries, a study originating in Asia could have a strong demonstration effect and prove very convincing for many Asian countries.